Analysis of Consumer Perceptions of Product Quality, Sales Promotion, and Ease of Purchase in Increasing Purchasing Decisions at Start-up Companies in Indonesia - Khuan, Hendri; Rahmiyati , Nekky; Mendrofa, Kristiurman Jaya; Santi Diwyarthi, Ni Desak Made; Mas Wiartha, Nyoman Gede (West Science Interdisciplinary Studies, 2024)
This research investigates consumer perceptions of product quality, sales promotion, and ease of purchase in the context of start-up companies in Indonesia. A quantitative research design, employing a sample of 150 participants, explores the relationships between these factors and their collective impact on consumer purchasing decisions. The study utilizes a cross-sectional survey approach, including demographic variables, and employs statistical analysis, including correlation and regression analyses with SPSS. The findings highlight the significance of product quality, sales promotion, and ease of purchase in shaping consumer preferences. Product quality emerges as the strongest influencer, followed by sales promotion and ease of purchase. Demographic variations further emphasize the need for tailored marketing strategies. The research contributes valuable insights for start-ups aiming to navigate Indonesia's diverse consumer landscape.